Perceptions and experiences of police officers and social workers within saps when assisting women who survived sexual violence in Mamelodi, Pretoria - Bahula, Ikageng (My University, 2023)
Many women are often reluctant to disclose cases of sexual violence to healthcare workers, police officers, family members etc. mainly due to the stigma attached. Few studies have been conducted to explore the experiences and perceptions of different role players within South African Police Officers (SAPS) when assisting women who survived sexual violence. Therefore, this study aimed to explore the perceptions and experiences of police officers and social workers within SAPS when assisting women who survived sexual violence. This study adopted a qualitative research approach, specifically a multiple case study design. The feminist poststructuralist theory was employed to guide the study. Three different interview guides were used as the research instrument. Individual face-to-face semi-structured interviews were used as the method of data collection. The sample size comprised twenty-five (25) different role players within SAPS in Mamelodi, Pretoria; five (5) client service centre police officers who work at both Mamelodi east and west police stations; ten (10) police officers who work in the special unit addressing sexual violence (FCS) at Mamelodi and ten (10) social workers who assist the survivors of sexual violence at both Mamelodi east and west police stations. The data gathered from the research were analysed using thematic analysis. The research showed that some participants perceived sexual violence in different ways. The study revealed that social workers, CSC police officers and police officers at FCS play different roles within SAPS. Participants portrayed that they encounter challenges in when handling cases of sexual violence for instance, lack of resources and support. Participants also complained of too much workload, trauma that comes with handling of sexual violence cases and that survivors withdraw the reported cases of sexual violence. Additionally, Participants reported that media and awareness campaigns encourages women to seek social work services. The study showed that some police officers are not aware of the strategies that exist with SAPS to address cases of sexual violence. Participants reported that they undergo certain trainings in order to equip themselves with knowledge on handling cases of sexual violence. This study may provide valuable insights into the experiences of police officers and social workers when handling cases of sexual violence as well as the strategies adopted by SAPS to address sexual violence cases in order to strengthen the support offered to women who are survivors of sexual violence.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Arts in Social Work to the Faculty of Humanities, University of the Witwatersrand, 2023
Keywords: Sexual violence; South African Police Service; Social Work